Preclinical Testing of Boron-Doped Diamond Electrodes for Root Canal Disinfection—A Series of Preliminary Studies - Koch, Maximilian; Palarie, Victor; Koch, Lisa; Burkovski, Andreas; Zulla, Manuel; Rosiwal, Stefan; Karl, Matthias (Microorganisms, 2022)
While numerous approaches have meanwhile been described, sufficient disinfection of root canals is still challenging, mostly due to limited access and the porous structure of dentin. Instead of using different rinsing solutions and activated irrigation, the electrolysis of saline using boron-doped diamond (BDD) electrodes thereby producing reactive oxygen species may be an alternative approach. In a first step, experiments using extracted human teeth incubated with multispecies bacterial biofilm were conducted. The charge quantities required for electrochemical disinfection of root canals were determined, which were subsequently applied in an animal trial using an intraoral canine model. It could be shown that also under realistic clinical conditions, predictable disinfection of root canals could be achieved using BDD electrodes. The parameters required are in the range of 5.5 to 7.0 V and 9 to 38 mA, applied for 2.5 to 6.0 min with approximately 5 to 8 mL of saline. The direct generation of disinfective agents inside the root canal seems to be advantageous especially in situations with compromised access and limited canal sizes. The biologic effect with respect to the host reaction on BDD-mediated disinfection is yet to be examined.
CRIS-Team Scopus Importer:2022-04-22
Keywords: antimicrobial treatment; canine tooth model; electrochemical disinfection; endodontics; reactive oxygen species